Pergolakan Elite dalam Panggung Politik di Bali 1945-1950 - I Made Sendra, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The political violence in Bali period 1946-1950, due to thedifferences of ideology, tactic, and the goal of struggle, betweentraditional elite against republican elites. The traditional elites(the monarch in Bali) who adopted cooperative-federalismaimed to establish The United Indonesia Republic accord toDutch commonwealth. Involving Bali as part of East IndonesiaState`s territory could maintain the status quo of Bali`smonarchy as traditional monarch. Otherwise, the republicanelites who adopt the unitary state and non-cooperative aimthat Bali tied together with The Republic of Indonesia`sterritory, because East Indonesia State was establised by Dutchgovernment.The signatory to the Linggarjati treaty caused for theexistence of Republic of Indonesia`s territory beyond Java,such as, Madura and Sumatra became uncertain. Thismoment is exploited by Dutch government (Van Mook) toconduct Denpasar Conference that succeeded to formulate theestablishment of the regulation of East Indonesia State. Since,Bali had belonged to the territory of East Indonesia State haschanged the situation that caused difficulties for armamentbattle in Bali. Therefore the Commander of The General HeadQuarter of The Indonesian People Struggle`s Council of SmallSundanese Area (Pimpinan Markas Besar Umum IndonesiaSunda Kecil) changed the strategy of struggle from militarypassive to diplomatic active through East Indonesia State`sParliament and General Assembly, as well.By the speech of East Indonesian State Parliament memberswho came from Bali, claimed that Bali to become consistently as part of Republic of Indonesia`s territory. As the Dutchgovernment transferred the sovereignty to United IndonesiaRepublic, the people coming from all over of East IndonesianRepublic demanded to dissolve United Indonesia Republic.Accordingly, the Balinese warrior youth claimed to dissolveBali`s Monarch Council (Dewan Raja Raja) and Bali`s GeneralAssembly (Paruman Agung) changed to be more democratic.In order to revert to unity and integrity of Indonesia,the government of United Indonesia Republic issued theEmergency Regulation Number 44/1950 that changedgovernment system from monarchy system to be moredemocratic system. That change is indicated by circulated theRepublican elite to be Bali`s Governor replaced the institutionof Bali`s Monarch Assembly (Dewan Raja Raja) and TheTemporary Parliament of Bali`s Province (Dewan PerwakilanRakyat Sementara) replacing the Bali`s General Assembly(Paruman Agung). The representative of political party whocame from republican elite became the member of TemporaryParliament of Bali`s Province.
Keywords: Traditional elite; republican elites; federalism; cooperative; commonwealth; non-cooperative; Monarch Assembly; General Assembly